Postoperative abdominal sepsis induces selective and persistent changes in CTCF binding within the MHC-II region of human monocytes - Siegler, Benedikt Hermann; Altvater, Marc; Thon, Jan Niklas; Neuhaus, Christopher; Arens, Christoph; Uhle, Florian; Lichtenstern, Christoph; Weigand, Markus A.; Weiterer, Sebastian (PLOS ONE, 2021)
Background Postoperative abdominal infections belong to the most common triggers of sepsis and septic shock in intensive care units worldwide. While monocytes play a central role in mediating the initial host response to infections, sepsis-induced immune dysregulation is characterized by a defective antigen presentation to T-cells via loss of Major Histocompatibility Complex Class II DR (HLA-DR) surface expression. Here, we hypothesized a sepsis-induced differential occupancy of the CCCTC-Binding Factor (CTCF), an architectural protein and superordinate regulator of transcription, inside the Major Histocompatibility Complex Class II (MHC-II) region in patients with postoperative sepsis, contributing to an altered monocytic transcriptional response during critical illness. Results Compared to a matched surgical control cohort, postoperative sepsis was associated with selective and enduring increase in CTCF binding within the MHC-II. In detail, increased CTCF binding was detected at four sites adjacent to classical HLA class II genes coding for proteins expressed on monocyte surface. Gene expression analysis revealed a sepsis-associated decreased transcription of (i) the classical HLA genes HLA-DRA, HLA-DRB1, HLA-DPA1 and HLA-DPB1 and (ii) the gene of the MHC-II master regulator, CIITA (Class II Major Histocompatibility Complex Transactivator). Increased CTCF binding persisted in all sepsis patients, while transcriptional recovery CIITA was exclusively found in long-term survivors. Conclusion Our experiments demonstrate differential and persisting alterations of CTCF occupancy within the MHC-II, accompanied by selective changes in the expression of spatially related HLA class II genes, indicating an important role of CTCF in modulating the transcriptional response of immunocompromised human monocytes during critical illness.